(untitled) (Proceedings of Faculty of Civil Engineering, 2024)
The paper analyses the development of the urban structure of coastal settlements on the example of Milna on Brač, whose prosperity was marked by shipbuilding. The development stages of the place that gave Milna its characteristic features were examined, which can be observed in the changes in the settlement’s fabric. Given the rapid increase in the built environment of almost all coastal settlements, including Milna on Brač, it is imperative to investigate the development processes and changes in the morphology of these settlements to preserve their characteristic features and develop quality guidelines for further development.